(untitled) (Bangladesh Journal of Psychiatry, 2020)
Obsessive Compulsive Disorder (OCD) is a common disorder and usually runs a chronic course with waxing and waning course. It leads to pervasive impairments in multiple domains of life. The aim of the study was to assess the demographic characteristics of the OCD patients and symptom severity of this disorder. This was a cross-sectional study done in OCD clinic of outpatient department (OPD) of BSMMU, during the period from May, 2015 to April, 2017. Four hundred patients fulfilling the inclusion and exclusion criteria were selected consecutively. After taking written consent a predetermined questionnaire was filled for each patient through face-to-face interview. Then patients were evaluated covering the following areas: Axis I diagnoses (DSM-IV) and Y-BOCS severity scale. The results showed that, the mean age of the respondents was 26.6 (SD±9.9) years, ranging from 8 to 63 years. According to Y-BOCS symptoms severity used for adult patients found that majority (70%) of the patients had moderate to severe sufferings. Male had co-morbid anxiety disorders (panic disorder, agoraphobia, social phobia) more but female patients were found more depressive disorders. Female had more hypothyroidism, diabetes, skin disorders and hypertension than male. These demographic status, co-morbidity profile and symptoms severity can serve as the baseline data for a country like Bangladesh and further large scale, multi-centered study would better generalize the study results. Bang J Psychiatry December 2016; 30(2): 23-26